A workplace intervention program and the increase in HIV knowledge, perceived accessibility and use of condoms among young factory workers in Thailand - Aphichat Chamratrithirong; Kathleen Ford; Sureeporn Punpuing; Pramote Prasartkul (Taylor & Francis Group, 2017)
Vulnerability to Human Immunodeficiency Virus (HIV) infection among factory workers is a global problem. This study investigated the effectiveness of an intervention to increase AIDS knowledge, perceived accessibility to condoms and condom use among young factory workers in Thailand. The intervention was a workplace program designed to engage the private sector in HIV prevention. A cross-sectional survey conducted in 2008 to measure program outcomes in factories in Thailand was used in this study. The workplace intervention included the development of policies for management of HIV-positive employees, training sessions for managers and workers, and distribution of educational materials and condoms. A multi-level analysis was used to investigate the effect of HIV/AIDS prevention program components at the workplace on HIV/AIDS knowledge, perceived accessibility to condoms and condom use with regular sexual partners among 699 young factory workers (aged 18-24 years), controlling for their individual socio-demographic characteristics. Interventions related to the management and services component including workplace AIDS policy formulation, condom services programs and behavioral change campaigns were found to be significantly related to increased AIDS knowledge, perceived accessibility to condoms and condom use with regular partners. The effect of the HIV/AIDS training for managers, peer leaders and workers was positive but not statistically significant. With some revision of program components, scaling up of workplace interventions and the engagement of the private sector in HIV prevention should be seriously considered.